The Environmental Impacts of Water Projects of Iraq's Neighboring Countries according to the Principle of Good Neighborly - Gadhban Dhaidan, Researcher. Talib; Jabbar Kreidi Al- Qadi , Prof. Dr. Ali (Basra studies journal, 2024)
Iraq is connected with number of neighboring countries such as Turkey, Iran and Syria by joint international rivers, in addition to naval borders like those with Kuwait. These countries have established water and economic projects on the rivers and shared seas with Iraq, and if international law has granted countries the right to exploit their wealth and resources within their region, it was restricted to that right to observe the principles of international law, including the principles of good neighborhood. The rules of the international neighborhood have established new obligations, these obligations would be the solid base to determine international responsibility for all the actions any state undertakes within its region and affects neighboring countries. The study have found through the problem of research that the principle of good neighborhood is one of the binding principles of international law and it is a legal mean to protect neighborhood areas and reduce the effects of harmful environmental effects that are transmitted from one country to another. The researcher have revealed also that the projects of neighboring countries have violated the rules of good neighborhood due to the environmental damage that resulted in it, which requires international responsibility for those damages.